Analisis Smart Governance di Kota Makassar - Akhmad Affandi; Juanda Nawawi; Suhardiman Syamsu (Kolaborasi : Jurnal Administrasi Publik, 2023)
This study aims to examine and analyze smart governance in Makassar City and the factors that affect it. This research was a qualitative research method using descriptive data. Data collection techniques used were observation, interview and documentation, and the data were analyzed using qualitative descriptive analysis. The results of the study show that smart governance in Makassar City has not been maximized so far. The dimensions of smart governance include smart use of ICT, smart collaboration and participation, smart decision-making, and smart administration. Meanwhile, the factors affecting it include supporting factors and inhibiting factors. Supporting factors involve the support of technology and human resources as well as the support of stakeholders and social conditions of the community, while the inhibiting factors include less supportive service facilities and service systems as well as the changes of regulation.